Allocation of Power Losses with Distributed Generation using a Contribution of Generator to Load Pairs Technique in a Distribution System - OMOTOSO, Ebenezer Abiodun; ABORISADE, David Olugbenga; ADEBAYO, Isaiah Gbadegesin; AYANLADE, Samson Oladayo (ABUAD Journal of Engineering and Applied Sciences, 2025)
Nigeria’s power sector lacks a structured approach to allocating active power losses, impacting cost fairness and operational efficiency. The contribution of the generator-load pairs technique effectively ensures equitable loss allocation in power networks. This study applied the technique in a Nigerian distribution network integrated with distributed generation (DG) to enhance transparency in loss allocation, using the Imalefalafia 32-bus network as a case study. Power flow analysis was conducted using the backward/forward sweep method to solve the network’s power flow problem. The adopted loss allocation technique was then used to allocate active power losses among generators and loads based on their contributions. Results demonstrated accurate and transparent loss allocation, ensuring fairness. The findings confirm the technique’s suitability for Nigeria’s distribution network and its potential to enhance efficiency in DG-integrated systems. This study introduces an effective loss allocation framework tailored to Nigeria’s electricity network, providing a basis for fair active loss-sharing mechanisms.